Appropriateness of Antibiotic Prescriptions in Chinese Primary Health Care and the Impact of the COVID-19 Pandemic: A Typically Descriptive and Longitudinal Database Study in Yinchuan City - Zhao, Houyu; Wang, Shengfeng; Meng, Ruogu; Liu, Guozhen; Hu, Jing; Zhang, Huina; Yan, Shaohua; Zhan, Siyan (Frontiers in Pharmacology, 2022)
Background The appropriateness of antibiotic prescriptions in primary care has not been well evaluated in China in recent years. Furthermore, the impact of coronavirus disease 2019 (COVID-19) on antibiotic prescriptions has not yet been investigated in China. We aimed to assess the appropriateness of antibiotic prescriptions and to evaluate the potential association between the COVID-19 pandemic and antibiotic prescriptions in primary care settings of Yinchuan, a city in China. Methods This study included 155 primary care institutions and 10192713 outpatient visits. Outpatient prescriptions were classified as appropriate, potentially appropriate, inappropriate, or not linked to any diagnosis indicating antibiotic use following a validated evaluation scheme. Interrupted time-series analyses were performed to assess the effects of the COVID-19 pandemic on antibiotic prescriptions in Chinese primary care facilities. Results During the study period, 1287678 (12.6%, 95% confidence interval [12.6–12.7]) of 10192713 outpatient visits in primary care resulted in antibiotic prescriptions. Among 1287678 antibiotic prescriptions, 653335 (50.7% [50.6–50.9]) were inappropriate, 463081 (36.0% [35.8–36.1]) were potentially appropriate, 171056 (13.3% [13.1–13.5]) were appropriate, and 206 could not be linked to any diagnosis. Furthermore, patient, physician, and institutional factors were associated with inappropriate antibiotic prescriptions; there was an overall decreasing trend in the proportions of inappropriate antibiotic prescriptions, with the highest level in 2017 (67.1% [66.8–67.5]) and the lowest in 2021 (40.8% [40.3–41.3]). A total of 1416120 individual antibiotics were prescribed, of which 1087630 (76.8%) were broad-spectrum and 777672 (54.9%) were classified in the World Health Organization’s “Watch” category. In addition, the COVID-19 pandemic was associated with changes of -2.8% (-4.4 – -1.3) in the level and 0.3% (0.2–0.3) in the monthly trend of antibiotic prescription rates, as well as changes of -5.9% (-10.2 – -1.5) in the level and 1.3 (1.0–1.6) in the monthly trend of the proportions of inappropriate antibiotic prescriptions. Conclusion More than half of the antibiotic prescriptions were inappropriate during the study period in primary care in Yinchuan. The COVID-19 pandemic may be associated with a decrease in the overall and inappropriate use of antibiotics in primary care settings in China.